Adolescent Cannabis Use Increases Risk for Cocaine-Induced Paranoia - Kalayasiri, Rasmon (2009)
Cannabis can produce and/or exacerbate psychotic symptoms in vulnerable individuals. Early exposure to cannabis, particularly in combination with genetic factors, increases the risk of a subsequent, primary, psychotic disorder. Because paranoia is a common feature of stimulant abuse and cocaine dependent individuals frequently endorse a history of cannabis abuse, we examined whether early cannabis exposure, in conjunction with polymorphic variation in the catechol-O-methyl transferase gene (COMT Val158Met), influences the risk for cocaine-induced paranoia (CIP). METHODS: Cannabis-use history was obtained in 1140 cocaine-dependent individuals from a family-based (affected sibling pair) study using the Semi-Structured Assessment for Drug Dependence and Alcoholism (SSADDA). Logistic regression and generalized estimating equations analyses were used to examine the role of adolescent-onset cannabis use (≤ 15 yrs of age) on CIP risk, both controlling for previously implicated CIP risk factors and familial relationships, and considering potential interactions with COMT Val158Met genotype. RESULTS: Cocaine-dependent individuals who endorsed CIP had significantly higher rates of adolescent-onset cannabis use than those without CIP (62.2% vs. 50.2%; χ(2) = 15.2, df = 1, p < 0.0001), a finding that remained after controlling for sibling correlations and other risk factors. There were no effects of COMT genotype or genotype by early cannabis onset interactions. A modest (OR = 1.4) and nearly significant (p = 0.053) effect of CIP status in probands on CIP status in siblings was also noted. CONCLUSIONS: Adolescent-onset cannabis use increases the risk of CIP in cocaine dependent individuals. COMT genotype and its interaction with early cannabis exposure did not emerge as significant predictors of CIP. In addition, trait vulnerability to CIP may also be familial in nature.